2008
DOI: 10.1186/1743-422x-5-59
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the Human Immunodeficiency Virus type 1 activity by crude and purified human pregnancy plug mucus and mucins in an inhibition assay

Abstract: Background: The female reproductive tract is amongst the main routes for Human Immunodeficiency Virus (HIV) transmission. Cervical mucus however is known to protect the female reproductive tract from bacterial invasion and fluid loss and regulates and facilitates sperm transport to the upper reproductive tract. The purpose of this study was to purify and characterize pregnancy plug mucins and determine their anti-HIV-1 activity in an HIV inhibition assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…Based on the findings in this study, and in the studies referred to above, we find it most likely that TFF3 and perhaps also other TFFs, affect the viscoelastic properties of the CMP, thereby maintaining the ability of the CMP to protect against ascending infections from the vagina to the uterine cavity (5,9,26), yet the exact nature of TFF's interaction with mucins is still to be fully explained.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Based on the findings in this study, and in the studies referred to above, we find it most likely that TFF3 and perhaps also other TFFs, affect the viscoelastic properties of the CMP, thereby maintaining the ability of the CMP to protect against ascending infections from the vagina to the uterine cavity (5,9,26), yet the exact nature of TFF's interaction with mucins is still to be fully explained.…”
Section: Discussionsupporting
confidence: 55%
“…Initially, CMPs were collected from 16 women in active labor (cervical dilatation 4-10 cm) at the delivery wards of Aarhus University Hospital, Denmark. The median (range) age of the women included was 29.5 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) years, the median gestational age was 40 +1 weeks (38 +0 -42 +0 weeks) and median parity was 1.5 (1)(2)(3)(4). The CMPs were shed spontaneously or manually retrieved during vaginal exploration.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized and confirmed that salivary MUC5B and MUC7 [4], breast milk mucin (MUC1) [5] and cervical or pregnancy plug mucins [6] inhibited HIV-1 activity in an in vitro inhibition assay. We have also shown the inhibition of poxvirus activity by MUC1 [7].…”
Section: Introductionmentioning
confidence: 85%
“…Mucins provide the structural framework of the CMP, and the extraction of mucins for analysis is a challenging procedure. Therefore, guanidinium chloride has been generally used to extract mucins [7,5456]. As a reducing agent was not used in our protein isolation protocol, the mucins remain cross-linked to each other to a substantial degree and so are not represented to the extent that they are present in the CMP.…”
Section: Discussionmentioning
confidence: 99%
“…The CMP is a unique and sizable (approximately 10 gm) structure that forms physical and biochemical barriers for the microorganisms present in the vagina [6]. It has been demonstrated that mucin proteins in the CMP, such as MUC1, MUC2, MUC5AC, and MUC5B, profoundly inhibit the activity of human immunodeficiency virus type I [7]. The biological and physical integrity of the CMP is therefore critical for a successful pregnancy because its disruption can lead to ascending intra-amniotic infection, one of the leading causes of preterm birth [6,8].…”
Section: Introductionmentioning
confidence: 99%